2019
DOI: 10.1111/hsc.12858
|View full text |Cite
|
Sign up to set email alerts
|

The caring experience in multiple sclerosis: Caregiving tasks, coping strategies and psychological well‐being

Abstract: Informal caregivers play a crucial role in supporting persons with multiple sclerosis (MS), a neurodegenerative disease resulting in progressive worsening of physical and cognitive functioning. While research extensively showed that caregiving workload can be perceived as burdensome, little attention was devoted to the relation connecting workload and caregivers’ well‐being. Building on previous literature on stress and coping, the aim of this study was to test the mediational role of coping between caregivers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…There is an extensive body of quantitative evidence highlighting that MS may threaten both the patients’ and their caregivers’ well-being, also depending on the level of accumulated disability [ 24 , 25 , 26 ]. However, it cannot be neglected that the caring experience lived by the families can be a powerful force towards adjustment and should be more valued by the physicians [ 27 , 28 ]. As a matter of fact, taking care of a person with MS does not entail only negative, but also positive aspects [ 29 ]: discovering personal and family resources, embrace change and apply coping strategies, such as supportive engagement and positive reframing.…”
Section: Introductionmentioning
confidence: 99%
“…There is an extensive body of quantitative evidence highlighting that MS may threaten both the patients’ and their caregivers’ well-being, also depending on the level of accumulated disability [ 24 , 25 , 26 ]. However, it cannot be neglected that the caring experience lived by the families can be a powerful force towards adjustment and should be more valued by the physicians [ 27 , 28 ]. As a matter of fact, taking care of a person with MS does not entail only negative, but also positive aspects [ 29 ]: discovering personal and family resources, embrace change and apply coping strategies, such as supportive engagement and positive reframing.…”
Section: Introductionmentioning
confidence: 99%
“…By examining patterns of use of the website, we will also be able to add to the understanding of the issues and concerns that are of most interest to caregivers of persons with multiple sclerosis. Although previous research has provided some descriptive data [ 6 , 8 , 10 ], these studies have primarily focused on describing poor psychological outcomes [ 4 , 5 , 14 , 15 ], coping strategies [ 7 , 9 , 13 ], or stressors [ 6 , 18 , 20 ], identified by caregivers of persons with multiple sclerosis. We will be able to identify topics of most interest (eg, self-care activities) and questions of greatest concern (eg, “How is multiple sclerosis treated?”) elicited directly from website usage of caregivers of persons with multiple sclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Investigators for the project who had expertise in the areas of caregiving (SLD and ARL), multiple sclerosis (MP, TP, and MJL), and website interventions (TP and MJL) developed the content for the project. The development of the video vignettes was based on previous research that identified the unique needs of caregivers of persons with multiple sclerosis [ 5 , 7 - 10 , 21 , 22 ], general caregiving research [ 26 - 31 ], and answers to a series of questions emailed to caregivers of persons with multiple sclerosis. The website developers oversaw the development and testing of the video vignettes and the overall website.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Family members and friends of persons with OD may also be negatively affected by the condition, since they are frequently involved in the care process as informal caregivers, a term referring to individuals who provide practical and/or emotional support without payment [ 13 ]. Regardless of OD etiology, caring for persons with OD may result in remarkable physical and emotional burden [ 14 20 ].…”
Section: Introductionmentioning
confidence: 99%